Dissonances and disconnects: the life and times of community-based accountability in the National Rural Health Mission in Tamil Nadu, India - Rakhal Gaitonde; Miguel San Sebastian; Anna-Karin Hurtig (BMC, 2020)
Abstract Background There are increasing calls for developing robust processes of community-based accountability as key components of health system strengthening. However, implementation of these processes have shown mixed results over time and geography. The Community Action for Health (CAH) project was introduced as part of India's National Rural Health Mission (now National Health Mission) to strengthen community-based accountability through community monitoring and planning. In this study we trace the implementation process of this project from its piloting, implementation and abrupt termination in the South Indian state of Tamil Nadu. Methods We framed CAH as an innovation introduced into the health system. We use the framework on integration of innovations in complex systems developed by Atun and others. We used qualitative approaches to study the implementation. We conducted interviews among a range of individuals who were directly involved in the implementation, focusing on the policy making organizational level. Results We uncover what we have termed "dissonances" and "disconnects" at the state level among individuals with key responsibility of implementation. By dissonances we refer to the diversity of perspective on the concept of community-based accountability and its perceived role. By disconnects we refer to the lack of spaces and processes for "sense-making" in a largely hierarchically functioning system. These constructs we believe contributes significantly to making sense of the initial uptake and the subsequent abrupt termination of the project. Conclusions This study contributes to the overall field of policy implementation, especially the phase between the emergence on the policy agenda and its incorporation into the day to day functioning of a system. It focuses on the implementation of contested interventions like community-based accountability, in Low- and Middle-income country settings undergoing transitions in governance. It highlights the importance of "problematization" a dimension not included in most currently popular frameworks to study the uptake and spread of innovations in the health system. It points not only to the importance of diverse perspectives present among individuals at different positions in the organization, but equally importantly the need for spaces and process of collective sense-making to ensure that a contested policy intervention is integrated into a complex system.